Modification of CSE-UCLA and Discrepancy as a New Evaluation Model in Education - P. Wayan Arta Suyasa; Dewa Gede Hendra Divayana (Ital Publication, 2021)
The absence of an evaluation model that can be used to evaluate the effectiveness of educational activities at vocational universities in the view of six domains causes the need to find innovations in an evaluation model. The six domains, included: context, input, socialization process, implementation process, results, and imbalances that occur in the learning implementation. An evaluation model innovation was initiated through this research in the form of a modification of two educational evaluation models. Those models are CSE-UCLA and Discrepancy. Based on those conditions, the main objective of this research was to demonstrate the existence of a new evaluation model design in education which was a modification of the CSE-UCLA evaluation model and the Discrepancy evaluation model. Specifically, this evaluation model design can be used to determine the effectiveness of the one education activity namely the synchronous learning implementation at vocational universities. The research method used to achieve the objectives of this research was the development method by the Borg and Gall model development design. Five stages of development become the focus of this research, included: research and field data collection, research planning, design development, initial trials, and main product revision. The location of this research was conducted in several vocational universities in the North Bali area (Indonesia). Subjects involved in the initial trials toward this evaluation model design were 20 people. The tools used to conduct the initial trials were questionnaires. The technique used to analyze the data of initial trial results was descriptive quantitative by comparing the percentage of the initial trial results with the standard percentage of the effectiveness level of modified model design. This research results indicate that the evaluation model design was categorized as effective by an effectiveness level was 81.93%. The implication of this research results was the existence of a new design of the educational evaluation model. This design combines two evaluation models to produce good functionality integration in determining the effectiveness level of the synchronouslearning implementation in all universities generally and in vocational universities in Bali particularly. Doi: 10.28991/esj-2021-01321 Full Text: PDF